2009
DOI: 10.1111/j.1399-6576.2009.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxing music as pre‐medication before surgery: a randomised controlled trial

Abstract: Relaxing music decreases the level of anxiety in a pre-operative setting to a greater extent than orally administrated midazolam. Higher effectiveness and absence of apparent adverse effects makes pre-operative relaxing music a useful alternative to midazolam for pre-medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 34 publications
4
94
0
4
Order By: Relevance
“…In pre-operative settings, relaxing music is reported to reduce pre-operative anxiety to a greater extent than sedative oral pre-medication (Bringman et al, 2009). Furthermore, having children listen to music prior to and during procedures such as lumbar puncture (Nguyen et al, 2010) and when going through day surgery, adults is reported to reduce their anxiety (Nilsson et al, 2009).…”
Section: Even In the 19mentioning
confidence: 99%
“…In pre-operative settings, relaxing music is reported to reduce pre-operative anxiety to a greater extent than sedative oral pre-medication (Bringman et al, 2009). Furthermore, having children listen to music prior to and during procedures such as lumbar puncture (Nguyen et al, 2010) and when going through day surgery, adults is reported to reduce their anxiety (Nilsson et al, 2009).…”
Section: Even In the 19mentioning
confidence: 99%
“…Of the 49 studies that met our selection criteria, six were systematic reviews 2-7 , three were meta-analyses [8][9][10] , 33 were randomised clinical trials [13][14][15][26][27][28][29][30][32][33][34][35][36][37]44,47 and seven were non-randomised clinical trials 11,12,25,31,45,46 26,31,[35][36][37]43 .…”
Section: Resultsmentioning
confidence: 99%
“…Music therapy in surgery A vast number of studies have already investigated the impact of music on patient anxiety in pre-operative, post-operative and intra-operative settings of surgical procedures from several specialties 2,7,11,13,18,25,28,31,32,34,35,37,41 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed significantly lower HF components during music therapy than before therapy in patients with SMDC, which suggests that music therapy triggers the dominant state of sympathetic nervous activities. Previous studies have reported that relaxing music decreases the level of anxiety and reduces stress (Bringman et al 2009;Nilsson et al 2009). On the other hand, our results show that music therapy suppressed parasympathetic nervous activities during music therapy in patients with SMDC.…”
Section: Discussionmentioning
confidence: 99%